Analiza dyskursu polityki wokół obywatelskiej inicjatywy ustawodawczej na wybranych przykładach debat parlamentarnych - Wójcik, Szymon (Polityka i Społeczeństwo, 2021)
The article is an attempted analysis of the political discourse concerning citizens’ legislative initiatives. It allows one to see what happens at the interface between the legislative and groups of citizens, which in rare and exceptional circumstances present their "grass-roots" legislative proposals. This interdisciplinary work combines political science and a qualitative sociological approach. The specific method used was Martin Reisgl’s political rhetoric analysis. Transcripts of parliamentary debate on the three selected citizens’ legislative proposals served as research material. The analysis showed an overall specificity of debates on citizens’ projects, but also confirmed the importance of the context in discourse studies. Discussion about each of the three – unique – citizens’ projects was shaped differently.